Cradle-to-gate water-related impacts on production of traditional food products in Malaysia - Bong P.X.H.; Malek M.A.; Mardi N.H.; Hanafiah M.M. (MDPI, 2023)
ecotoxicology; eutrophication; food market; food product; food production; life cycle analysis; probability; sustainability; water footprint; water pollution; Malaysia